2017
DOI: 10.17664/ksgee.2017.13.1.014
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Underground Thermal Environment around Wells for a Design Method of Open-Loop Geothermal System

Abstract: Groundwater heat pump (GWHP) system can achieve higher performance of the system by utilizing heat source of the annual constant groundwater temperature. The performance of GWHP system depends on the ground thermal environment such as groundwater temperature, groundwater flow rate and hydraulic conductivity. In this study, the geothermal environment was analyzed by using numerical simulation for develop the two-well geothermal system. As the result, this paper shows the change of the groundwater level and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Park et al [12] investigated the isotopic compositions and chemical of groundwater as the GWHP system was operated to understand its geochemical properties. Bae et al [13] set the operation and ground as case conditions and quantitatively showed the changes of groundwater level and groundwater temperature according to the operation of a multi-well system. However, when a multi well open-loop system is used for a long term, there is a concern that clogging may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [12] investigated the isotopic compositions and chemical of groundwater as the GWHP system was operated to understand its geochemical properties. Bae et al [13] set the operation and ground as case conditions and quantitatively showed the changes of groundwater level and groundwater temperature according to the operation of a multi-well system. However, when a multi well open-loop system is used for a long term, there is a concern that clogging may occur.…”
Section: Introductionmentioning
confidence: 99%
“…지상으로 양수된 가열된 물은 열 교환기를 거쳐서 증기터빈을 이용 하여 전기를 생산한다 (Jiang et al, 2016;Lee and Chung, 2020). 대표적으로 낮은 투수성을 가진 기반암은 화강암으 로 (Chandrasekharam et al, 2015) (Carlson et al, 2018;Nouraliee, 2000) (Scherff, 2016;Cladouhos et al, 2016 (Bae et al, 2017;Park et al, 2013) 공급하는 지열발전소로서 수십 년 동안 가동되어 왔다 (Sahar et al, 2010;Mutonga, 2007 Caulk et al, 2016;Luo et al, 2018).…”
unclassified